Optimisation and Characterisation of Curcumin Nanoparticles with Chitosan-TPP Combination Using Ionic Gelation Method as a Cut Wound Healer - setyawan, Ferdinta D; Kuncahyo, Ilham; Herdwiani, Wiwin (East Asian Journal of Multidisciplinary Research, 2024)
Curcumin has low oral bioavailability, low solubility, and is easily degraded, making its clinical application difficult. This study aims to determine the effect of optimum concentration and formula of chitosan and TPP in the preparation of curcumin nanoparticles on particle size, zeta potential, adsorption efficiency, and incision wound healing. The optimisation method used simplex lattice design method. There were 8 draft formulas consisting of a combination of chitosan and TPP. Each formula was tested for zeta potential value, adsorption efficiency, particle morphology, and wound healing ability. The optimum formula was then determined and analysed using the simplex lattice design method. The combination of chitosan and TPP with simplex lattice design gives an influence on curcumin nanoparticles which reduces particle size, gives a negative zeta potential value, increases the sorption efficiency of the active substance (curcumin) and accelerates the healing effect of cut wounds in mice. The proportion of chitosan and TPP that can produce the optimum formula using simplex lattice design on the critical parameters of particle size, zeta potential value, sorption efficiency and wound healing ability is chitosan.